Mr. Tiger goes wild - Brown, Peter, 1979- (New York : Little, Brown and Company, 2013)
Bored with city life and the proper behavior it requires, Mr. Tiger has a wild idea that leads him to discover his true nature.
Keywords: Self-actualization -- Fiction; Etiquette -- Fiction; CIty and town life -- Fiction; Tigers -- Fiction; Big cats -- Fiction